The rise of digital sex work - Fowler, Kurt (Alternative criminology, 2023)
"Written in a clear, accessible voice, Virtually Yours is an intimate look into the changing face of sex work on the internet, telling the stories of workers themselves - how they share information, grow their business, and build a worldwide sex worker community"--